Quantifying the Surface Energy Fluxes in South Greenland during the 2012 High Melt Episodes Using In-situ Observations - Fausto, Robert S.; van As, Dirk; Box, Jason E.; Colgan, William; Langen, Peter L. (Frontiers in Earth Science, 2016)
Two high melt episodes occurred on the Greenland ice sheet in July 2012, during which nearly the entire ice sheet surface experienced melting. Observations from an automatic weather station (AWS) in the lower ablation area in South Greenland reveal the largest daily melt rates (up to 28 cm d-1 ice equivalent) ever recorded on the ice sheet. The two melt episodes lasted 6 days, equivalent to 6% of the June-August melt period, but contributed 14 % to the total annual ablation of 8.5 m ice equivalent. We employ a surface energy balance model driven by AWS data to quantify the relative importance of the energy budget components contributing to melt through the melt season. During the days with largest daily melt rates, surface turbulent heat input peaked at 552 Wm-2, 77 % of the surface melt energy, which is otherwise typically dominated by absorbed solar radiation. We find that rain contributed ca. 7 % to melt during these episodes.